Problem:
Evaluate cos-1(u)+csc-1(v) where u and v are the solution to the system:
ln(v)=-(1/2)ln(u)
2log2(u)=2log2(v)=-3
Work so far:
log2(u2)=log2(v2)-3 ----> log2(u2/v2)=-3 ---> 2-3=(u2/v2) --> (1/8)=(u2/v2)
Not sure what to do next... also confused about how ln rules work compared to log rules.
Evaluate cos-1(u)+csc-1(v) where u and v are the solution to the system:
ln(v)=-(1/2)ln(u)
2log2(u)=2log2(v)=-3
Work so far:
log2(u2)=log2(v2)-3 ----> log2(u2/v2)=-3 ---> 2-3=(u2/v2) --> (1/8)=(u2/v2)
Not sure what to do next... also confused about how ln rules work compared to log rules.